DETERMINANTS ANALYSIS OF EARLY NEONATAL DEATH AGE 0-7 DAYS IN EAST NUSA TENGGARA PROVINCE (NTT) - Syaharasyi, Rayyan; Abdullah, Asnawi; Dharina, Dharina; Adamy, Aulina; Fajriana, Eulisa (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2023)
Background: Neonatal mortality is one of the focuses of world health problems, one of the goals of the Millennium Development Goals (MDGs). The neonatal mortality rate in Indonesia was higher than in 2 Asian countries such as Thailand and Malaysia in 2014. The neonatal mortality rate in NTT Province is quite high, at 26/1000 live births, compared to the national rate of 20/1000 live births. This study aim to determine the relationship between early neonatal death 0-7 days in NTT and several influencing determinants. Method: This study used a descriptive-analytical method with a case-control design. The data used are secondary data by AIPMNH (Australian International Partnership of Maternal and Neonatal Health). The population in this study were all neonates born in NTT Province from 220 villagesand70 health centers, consist of 154 cases, and 308 controls. Sampling using the case-control study formula was then grouped into ages 0-7 days so that 114 were obtained as case groups and 228 as control groups. Data collection was carried out for 9 months from January 1 to September 31, 2013, processed and presented in 2015 using a questionnaire through interviews, then the existing secondary data was reprocessed by researchers with different variables in 2018. Data analysis used the Logistic Regression test with the STATA 13 program. Results: The results of the study obtained variables related to Poverty (OR=2.12; P=0.006), Complications During Pregnancy (OR=3.41; P=0.003), Complications During Birth (OR=3.89; P=0.000), Having a Disease During Pregnancy (OR=1.61; P=0.091), Gravida (OR=2.88; P=0.014), Abortion (OR=2.27; P=0.056), IMD (OR=9.69; P=0.000), Place of Birth (OR=5.23; P=0.000), and Health Services (OR=5.23; P=0.000). Furthermore, based on the multivariate analysis of IMD (OR=8.71; P=0.000), Pregnancy Complications (OR=2.97; P=0.040), and Poverty (OR=2.16; P=0.041) are the most influential factors in early morning neonatal deaths in the East Nusa Tenggara (NTT) region. Recommendation: It is expected that the Leader (Governor) of NTT Province and NTT Central Health Officers will provide more counseling and guidance to mothers to increase their knowledge about pregnancy and neonatal.